Determinants of Knowledge, Attitude, and Practices of Veterinary Drug Dispensers toward Antimicrobial Use and Resistance in Main Cities of Malawi: A Concern on Antibiotic Stewardship - Henson Kainga; Marvin Collen Phonera; Ibrahim Chikowe; Elisha Chatanga; Hlupikire Nyirongo; Mike Luwe; James Mponela; Vincent Kachisi; Nathani Kamanga; Julius Chulu; Gilson Njunga; Daisy Nabadda; et al. (MDPI AG, 2023)
Antimicrobial resistance (AMR) is an emerging challenge to global public health. The use of antibiotics in the veterinary field is one of the contributing factors to AMR mostly due to poor knowledge, attitudes, and practices (KAP) of dispensers. Veterinary drug dispensers are expected to guide clients on indications, contraindications, and withdrawal periods of veterinary drugs. This study assessed veterinary drug dispensers' KAP toward AMR and associated potential contributing factors. A cross-sectional study, using a structured questionnaire, was conducted in three main cities of Malawi, namely Mzuzu, Lilongwe, and Blantyre. A total of 68 agrovet shops were selected using a simple random sampling technique. The KAP level was presented descriptively. Bivariate and multivariable analyses were run to investigate the relationships between the independent and outcome variable. Overall, the KAP score for knowledge, attitude, and practices was 46.7%, 49.2%, and 41.6%, respectively. The significant determinants of the knowledge were the practice of asking for a written prescription (OR: 16.291, 95% CI: 11.6-24.2) (p = 0.024), female (OR: 0.609, 95% CI: 0.3-0.9) (p = 0.001), and old age (≥35) (OR: 0.227, 95% CI: 0.1-0.5) (p = 0.04). Poor knowledge, negative attitude, and poor practices were observed among most of the participants. Sensitization and training on AMR and antimicrobial stewardship are recommended to address the KAP score gaps and the observed determinants among veterinary drug dispensers.